Sawdust Ash as Powder Material for Self-Compacting Concrete Containing Naphthalene Sulfonate - Augustine U. Elinwa; Ahmed M. Mamuda (Advances in Civil Engineering)
Tests are carried out to determine the fluidity of Ashaka Portland cement paste and its compatibility with sawdust ash (SDA) as powder material for self-compacting cement (SCC) mixtures. Results of the investigation showed that saturation was achieved at w/c ratios of 0.4 and 0.42, at dosages of naphthalene sulfonate superplasticizers of 3.5% and 2%, respectively. The optimum replacement level for the SCC mixture was 10 wt.% of cement by SDA and 2% of the superplasticizer dosage. The achieved spread and flow time were 26 cm and 8 seconds and are within the specified range of 24 cm to 26 cm and 7 to 11 seconds, respectively. Statistical inference showed that the mix, w/c, and the interaction between the mix and w/c ratio are significant.